The nanoscale rock mechanical properties of different rank coal by nanoindentation test - Zhang, Y.; Lebedev, Maxim; Iglauer, Stefan (2018)
Copyright © 2018 ARMA, American Rock Mechanics Association. Fully understand the microstructures and the rock mechanical property are extremely important for the coal seam characterization, explorations, coal bed methane (CBM), enhanced coal bed methane (ECBM), and CO2 storage. However, how the different coal rank relate to the microstructure and rock mechanical property are still in-sufficient. Thus, in this study, we conducted the 3D high resolution microCT scanning (3.43 µm voxel sizes) and nanoindentation test on high to low rank coals – anthracite, bituminous, sub-bituminous, lignite, and peat. The coal microstructure are quantified after the image segmentation process which show the low rank coal has the most abundant pore system (including large pores and tiny pores) and high rank coal has the more fixed carbon content. Furthermore, the coal indentation modules decreased from high to low rank coal, we thus suggested the safety issues for the low rank coal seam should be in priority concern.